2022
DOI: 10.1186/s12874-022-01562-4
|View full text |Cite
|
Sign up to set email alerts
|

Developing a tool to assess the skills to perform a health technology assessment

Abstract: Background Health technology assessment (HTA) brings together evidence from various disciplines while using explicit methods to assess the value of health technologies. In resource-constrained settings, there is a growing demand to measure and develop specialist skills, including those for HTA, to aid the implementation of Universal Healthcare Coverage. The purpose of this study was twofold: a) to find validated tools for the assessment of the technical capacity to conduct a HTA, and if none we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…HTA has been highlighted by the WHO as one of the tools that can propel countries towards UHC if implemented. Examples of countries recently introducing HTA in decision making include Ghana 15,18 , India 19 , Kenya 20 , Indonesia 21 , and the Philippines 22 . Uganda is committed to the achievement of UHC by 2030 through strengthening the health system and its support mechanisms with a specific focus on primary health care 23 .…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%
“…HTA has been highlighted by the WHO as one of the tools that can propel countries towards UHC if implemented. Examples of countries recently introducing HTA in decision making include Ghana 15,18 , India 19 , Kenya 20 , Indonesia 21 , and the Philippines 22 . Uganda is committed to the achievement of UHC by 2030 through strengthening the health system and its support mechanisms with a specific focus on primary health care 23 .…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%
“…9 The topic of how OSLASE helps the trainee to confirm the skills acquired emerged several times during the interviews, confirming the perception that assessment is an essential step in the consolidation and promotion of future practical learning. 29,30 The trainees also reported that the OSLASE establishes a standard and defines the skills that students are expected to develop in subsequent sessions. They also felt that demonstrations contributed to the identification of skills that should be improved and to the support of the role of those overseeing workplace training, which are crucial features introduced by the assessment in the context of these courses.…”
Section: Discussionmentioning
confidence: 99%
“…Atkeson et al (2014) argue that the presence of an interviewer can alter response patterns on questions that pertain to an individual's personal beliefs, attitudes, or experiences. Bidonde et al (2023) found that response rates of adolescents in studies of mental health can indeed vary with survey mode, consent type, and incentives used. Overall, it seemed that when there is any kind of supervision involved, response rates were at least slightly higher.…”
Section: Supervision During Self-administered Surveysmentioning
confidence: 98%
“…When surveys take place in schools, it is common practise to work with teachers as "assistant supervisors", as they are already figures of authority in the target groups and can usually handle group dynamics and disruptions. Although their ability to do so may vary (March et al 2022), this should increase data quality in terms of validity and completion rates (Bidonde et al 2023).…”
Section: Effects Of Teachers' Presencementioning
confidence: 99%